India's emerging foreign policies - "Kothari, Shantilal" (Bombay, 1951)
This book attempts to bring out salient features emerging out of the policy of Pandit Jawaharlal Nehru, the architect of modern India's foreign policy. There is a dearth of material on this subject. Many American, British and European writers have approached this subject but have failed to appreciate it from the Asian angle. Their impressions, their source materials, their approach, their conclusions were colored. For instance Japan has always been brought before us as an "undesirable" Asian Power. For an Asian, it is difficult to see the logic in branding Japan as an inherently dangerous power.
Keywords: India foreign relations